2018
DOI: 10.1177/2331216518783608
|View full text |Cite|
|
Sign up to set email alerts
|

Do Hearing Aids Address Real-World Hearing Difficulties for Adults With Mild Hearing Impairment? Results From a Pilot Study Using Ecological Momentary Assessment

Abstract: Current approaches to the measurement of hearing aid benefit typically use clinical or laboratory-based speech perception tests or retrospective self-report surveys. However, when assessing hearing aid outcomes in adults with mild hearing impairment, the traditional outcome measures may not be sufficiently sensitive. An alternative to these techniques are approaches that capture data about real-world experiences as they are experienced, such as ecological momentary assessment. This single-subject experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 46 publications
1
27
1
Order By: Relevance
“…In relation, it is likely that participants had varied listening experiences, which could have influenced the outcomes of the study. Although our aim was to understand the everyday experiences of people living with hearing loss toward smartphone-connected listening devices, information regarding the listening situations encountered by participants could be measured in future studies, such as via hearing diaries, data logging, or ecological momentary assessment (for recent application, see Timmer et al, 2018). Logistical reasons also necessitated the use of a convenience sampling strategy, which is potentially less rigorous than other qualitative sampling techniques.…”
Section: Study Limitations and Future Researchmentioning
confidence: 99%
“…In relation, it is likely that participants had varied listening experiences, which could have influenced the outcomes of the study. Although our aim was to understand the everyday experiences of people living with hearing loss toward smartphone-connected listening devices, information regarding the listening situations encountered by participants could be measured in future studies, such as via hearing diaries, data logging, or ecological momentary assessment (for recent application, see Timmer et al, 2018). Logistical reasons also necessitated the use of a convenience sampling strategy, which is potentially less rigorous than other qualitative sampling techniques.…”
Section: Study Limitations and Future Researchmentioning
confidence: 99%
“…Recent evidence supports the application of EMA within hearing research and has demonstrated the success with which EMA methods and technologies are adopted by individuals with HI (e.g., Galvez et al 2012 ; Henry et al 2012 ; Timmer et al 2017 ). EMA has been used to successfully measure and classify auditory context and to assess HA outcomes in real-world settings (e.g., Hasan et al 2014 ; Wu et al 2015 ; Smeds et al 2018 ; Timmer et al 2018 ; Jensen et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is not uncommon for EMA studies to pool data from both types of surveys to answer research questions. 8,9,24 Comparisons: Test versus Retest…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the use of EMA in audiology research has grown in the past decades. EMA has been implemented using paper-and-pencil journals, [2][3][4][5] daily diaries, 6 portable computers, 7 and smartphones 8,9 to assess hearing difficulty or hearing aid outcomes in the real world.…”
mentioning
confidence: 99%